2021
DOI: 10.1096/fj.202002448r
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling is an essential regulator of endometrial proliferation and implantation in mice

Abstract: Insulin-like growth factor 1 receptor (IGF1R), along with insulin receptor (INSR), belong to class II receptor tyrosine kinase superfamily. They have high structural homology, as well as identity ranging from 45 to 65% in the ligand-binding domain, 65-85% in the tyrosine kinase domain. 1,2 Both receptors form heterotetramers comprised of two extracellular alpha subunits and two transmembrane beta subunits bound by disulfide bridges. 3 One of the consequences of such a high degree of homology is the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…INSR has been validated as a polycystic ovary syndrome risk locus using a very large, well-designed case-control GWAS ( Shi et al, 2012 ). Meanwhile, INSR has been confirmed to be necessary for optimal endometrial proliferation and implantation ( Sekulovski et al, 2021 ). Furthermore, INSR plays a crucial role in controlling adipose tissue development and adipocyte survival ( Boucher et al, 2012 ; Cignarelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…INSR has been validated as a polycystic ovary syndrome risk locus using a very large, well-designed case-control GWAS ( Shi et al, 2012 ). Meanwhile, INSR has been confirmed to be necessary for optimal endometrial proliferation and implantation ( Sekulovski et al, 2021 ). Furthermore, INSR plays a crucial role in controlling adipose tissue development and adipocyte survival ( Boucher et al, 2012 ; Cignarelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated miR-328-3p is a biomarker in teratozoospermia and may decrease fertilization and embryo formation rate ( Corral-Vazquez et al, 2019 ). Moreover, for the three common DEmiRs between human and mouse sperm, it is reported that overexpression of miR-140-5p significantly inhibits cell proliferation and promotes cell apoptosis in chronic myeloid leukemia cells ( Geng et al, 2020 ; Jiao et al, 2020 ), while miR-30b-5p can promote cell proliferation and cell cycle progression in cancer ( Qin et al, 2017 ), and miR-148b-3p is correlated with fertility rate ( Chen et al, 2018 ; Sekulovski et al, 2021 ). More importantly, in our study, downregulation of miR-148b-3p, according to qRT-PCR analysis, in both human and mouse frozen-thawed sperm may still affect the expression of miR-148b-3p during subsequent embryonic development, leading to the significantly lower embryo formation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dual receptor ablation compromised decidualization, reduced endometrial thickness, and inhibited embryo implantation. Authors further observed decreased activation of ERK/MAPK signaling ( Sekulovski et al, 2021 ). Other pathological states, such as inflammation and obesity, cause insulin resistance by serine phosphorylation of the insulin receptor or insulin receptor substrate (IRS) proteins by TNF-α and PKCε ( Hotamisligil, 1999 ).…”
Section: Introductionmentioning
confidence: 93%